Issues and coping strategies of families with cancer patient member - Lopez, Valerainne Reyes
The study investigated the coping strategies of families with cancer patient member. Issues on psychological, emotional, social and financial aspects were considered in the study. The study also described the behavioral changes affecting the family members specifically on family relationships. Subjects were ten (10) families with female cancer patient member afflicted with different types of cancer from Bataan selected through purposive sampling. The respondents were between the ages of 35 and 56 years. Responses of the respondents were subjected to frequency and content analysis. Findings of the study showed that families with cancer patient member used the following strategies: participating in religious groups, joining a cancer support group and seeking financial assistance from relatives and organizations involved in the support of cancer patients to address the different issues and problems encountered by the family members. Cancer support groups emerged as an effective and positive measure for families with cancer patient member. Belonging to a group of people who had the same experience gives a feeling of security and belongingness in order to cope with the different issues such as psychological, emotional, social and financial issues. Findings of the study also revealed that families with cancer patient member became closer to one another and valued constant communication among the members to address the needs of the cancer patient.